The Initial Months of COVID-19: Dog Owners' Veterinary-Related Concerns - Kogan, Lori R.; Erdman, Phyllis; Bussolari, Cori; Currin-McCulloch, Jennifer; Packman, Wendy (Frontiers in Veterinary Science, 2021)
Veterinarians, like many other professions, were significantly impacted by the onset of COVID-19 in the spring of 2020. Standard practices were disrupted, and veterinary hospitals had to quickly modify standard protocols to safely serve their clients and patients. The purpose of this study was to better understand dog owners’ fears and concerns pertaining to veterinary care and obtainment of pet care products and food during the lock down phase of a pandemic to be better prepared to address these concerns now and in the future. To this end, an online, anonymous, cross-sectional survey was designed and distributed to adult dog owners via social media. The results, from a total of 4105 participants (the majority from the United States and Canada), indicated substantial areas of concern. The number one concern of dog owners during this time was the availability of emergency veterinary care. Owners under 30 years of age, compared to older owners, were significantly more concerned about both availability and cost of veterinary care (emergency and non-emergency). The ability to care for one’s dog if they were to become ill was a concern for many owners, yet only 60% had identified a caretaker for their dog if one was needed. These results suggest that the majority of dog owners remained true steadfast guardians of their dogs, continuing to make them a priority, even during pandemic times. Suggestions to help mitigate dog owners’ concerns and improve communication between owners and veterinarian teams are offered.